History Teaching in Vocational School Based on Curriculum 2013 - Ajat Sudrajat; Dyah Kumalasari; Danu Eko Agustinova (Yogyakarta State University, 2019)
The Curriculum 2013 is a learning guidance for schools in Indonesia. One among many schools that applied Curriculum 2013 is vocational school. Social sciences based majors also being taught in vocational school. One of them is Indonesian History. The major of history in vocational school is very strategic for internalizing national character values. Unfortunately, history teachers in vocational school don’t apply suitable way in their teaching. That’s understandable since students in vocational school focus on vocational majors. This research employs a descriptive qualitative method by utilizing some techniques of data collection such as observations, interviews and documentations. The aim of this research is to know teaching strategy which is suitable in vocational school. The benefit of this research is the finding of ideal teaching strategy for vocational school students. In this case, the object of research is SMK Negeri 3 Kudus. History teaching in vocational school can utilize teaching media and learning in historical site. Those two strategies have goal for easing students of vocational school in understanding material of history subject. Each of those strategies has advantages and downsides, so that combination of them can cover each others’ downsides.